Identifikasi Jenis Gulma Pada Area Lahan Pertanian Di Kecamatan Tugumulyo Sebagai Pengembangan Flipbook - Eliska, Andung (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2023)
This study aims to determine the types of weeds in the area of agricultural land in Tugumulyo District and developed as a flipbook for the community. The research method used is descriptive qualitative. Collecting data using purposive sampling technique and using the plot method. The results of research conducted in 8 (eight) villages in the District of Tugumulyo found 21 species from 9 weed families namely Axonopus compressus, Panicum repens, Eragrotis Mexicana, Eleusine indica L, Cynodon dactylon L, Echinochloa colona, Cyperus rotundus, Cyperus difformis L, Fimbristylis miliacea L, Cyperus kyllingia, Mimosa pudica, Alternanthera philoxeroides, Amaranthus spinosus L, Commelina diffusa L, Galinsoga parviflora, Ageratum conyzoides L, Mikania micrantha, Phyllanthus niruri, Cleome rutidospermae, Ludwigia erecta, Ludwigia oktovalvis. Flipbook validation results by 3 validators, namely material experts 82%, media experts 90% and linguists 87%. The results of the readability test on the community with a percentage of 89% stated that flipbooks were in the very good category and were suitable for use as a source of information and reading for the community